The systemic immune-inflammation index (SII) in predicting postoperative systemic inflammatory response syndrome (SIRS) after ureteroscopy - Yahşi, Sedat; Ceviz, Kazım (The European Research Journal, 2023)
Objectives: The predictive value of some preoperative inflammatory markers for postoperative infective complications in urinary system stone disease has been demonstrated. We investigated how valuable the systemic immune-inflammation index (SII) is as a marker for the development of postoperative systemic inflammatory response syndrome (SIRS) in patients undergoing ureteroscopy.Methods: The data of 495 patients who met the study criteria were evaluated retrospectively. The patients were divided into groups according to whether they developed SIRS postoperatively or not. The clinical and demographic data of the patient groups as well as blood parameters were evaluated.Results: Postoperative systemic inflammatory response syndrome was detected in 105 (21.2%) of the patients. Age, diabetes, cardiovascular disease, preoperative urinary culture positivity, SII, neutrophil-lymphocyte ratio (NLR), lymphocyte-monocyte ratio (LMR) and platelet-lymphocyte ratio (PLR) were found to be significant for the development of SIRS. When the areas under the curve were measured in the ROC analysis, it was seen that the SII, NLR, LMR and PLR had high predictive values for the development of SIRS (area under the curve values of 0.73, 0.76, 0.72 and 0.67, respectively). In the multivariate logistic regression analysis, among the risk factors, age, cardiovascular disease, preoperative urinary culture positivity and NLR were determined as independent risk factors.Conclusions: Study revealed that only NLR among inflammatory markers is an independent risk factor for the development of SIRS. Although there is a relationship between the preoperative SII and the development of SIRS, it is not an independent risk factor. Along with many other variables, it may contribute to the development of SIRS.